An investigation of hedonic methods applicability to analyzing prices of various groups of durable goods - Król, Anna (Badanie przydatności metod hedonicznych do analizy cen różnych grup dóbr trwałego użytku, 2015)
The paper summarizes empirical research finalizing the first stage of the scientific project aimed at hedonic methods application in adjusting price indices in cases when variability in quality of goods is observed. A hedonic model describes the price of the heterogeneous good by a set of its relevant attributes, and thus it can be helpful in distinguishing the price change level resulting from quality-related and other than quality-related causes. As a consequence, hedonic methods provide a group of potential solutions to the problem of measuring a socalled “true price change” by introducing quality-adjusted price indices. However, beforehand a reliable, stable and predictively powerful hedonic model must be constructed and estimated. The main goals of the presented research were: 1) to test whether the initially chosen goods are convenient for hedonic analyses; 2) to estimate and verify the hedonic models suitable for further analyses for goods selected in the first step. The empirical research was based on a database consisting of seventeen groups of durable goods (household appliances, consumer electronics and ICT/IT devices)
Ekonometria = Econometrics, 2015, Nr 3 (49), s. 33-44
Keywords: hedonic methods; durable goods; prices; metody hedoniczne; dobra trwałego użytku; ceny